Randomized phase II trial evaluating pain response in patients with spinal metastases following stereotactic body radiotherapy versus three-dimensional conformal radiotherapy. Issue 2 (August 2018) - Sprave, Tanja; Verma, Vivek; Förster, Robert; Schlampp, Ingmar; Bruckner, Thomas; Bostel, Tilman; Welte, Stefan Ezechiel; Tonndorf-Martini, Eric; Nicolay, Nils Henrik; Debus, Jürgen; Rief, Harald
Abstract: Background: To report the primary endpoint of a randomized trial comparing pain response following palliative stereotactic body radiation therapy (SBRT) versus conventionally-fractionated 3D-conformal radiotherapy (3DCRT) for previously untreated spinal metastases. Methods: Fifty-five patients with histologically/radiologically confirmed painful spinal metastases were analyzed in this single-institutional, non-blinded, randomized explorative trial. Participants were randomly assigned (1:1) to receive single-fraction SBRT (24 Gy) or 3DCRT (30 Gy in 10 fractions). The primary endpoint was pain relief of >2 points on the visual analog scale (VAS) measured within the irradiated region at 3 months following radiotherapy completion. Other recorded parameters included pain response (per International Bone Consensus response definitions), use of concurrent medications and opioid usage (oral morphine equivalent dose, OMED). All parameters were assessed at baseline and at three and six months after RT. Intention-to-treat analysis was applied. This trial is registered with ClinicalTrials.gov, number NCT02358720. Findings: Despite no significant differences for VAS at 3 months between groups ( p  = 0.13), pain values decreased faster within this time period in the SBRT arm ( p  = 0.01). At 6 months following RT, significantly lower VAS values were reported in the SBRT group ( p  = 0.002). There were no differences in OMED consumption at 3 ( p  = 0.761) and 6 months ( p  = 0.174). There was a trend toward improved pain response in the SBRT arm at 3 months ( p  = 0.057), but significantly so after 6 months ( p  = 0.003). No patient in the SBRT group experienced grade ≥3 toxicities according to the Common Terminology Criteria for Adverse Events v.4.03. Conclusions: This randomized trial demonstrates the utility of palliative SBRT for spinal metastases, which was associated with a quicker and improved pain response. Larger ongoing randomized studies will assist in further addressing these endpoints.